Investigating Correlation of Window’s Configuration of Classroom and Daylight Indicators in Hot and Arid Region of Kerman City - N. Daei Parizi; M. Nikpour; H. Fallah (Iranica Journal of Energy and Environment)
For reading and writing in classrooms therefore a lot of energy is consumed in educational spaces. Limitation of fossil fuels and environmental pollution are two subjects that demonstrate the importance and significance of the present study. Previous studies show that window size and configuration have a significant effect on daylight quality but numbers and the ways of expansion of windows in horizontal and vertical directions of the wall have not been investigated in classrooms in hot and arid regions of Kerman city. The objective of this paper is to evaluate the daylight indicators in different classrooms when different numbers of windows (from 1 window to 5 windows) are applied both horizontal and vertical expansion in each window area from (10%c WWR to 60% WWR). This research has been done through the simulation of different classrooms in Design Builder software under Kerman weather data. Validation of Design Builder has been evaluated through experimental measurement of two actual classrooms and comparing the simulation results and experimental data. The findings of this research demonstrated that using a greater number of windows in classrooms causes a decrease in the amount of daylight penetrating the classrooms.